PENGARUH PROFESIONALISME, ETIKA PROFESI DAN PELATIHAN AUDITOR TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI BALI - Satwika Adhi Nugraha, Ida Bagus; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
Good performance of auditors will help public accounting firm to achieve the goals and meet the needs of the parties interested in the financial statements. Auditors are required to be an expert to be able to retain the trust of its clients and of the other users of audited financial statements. Auditor training can improve the ability of auditors to do the job in the audit process. The purpose of this study was to determine the effect of professionalism, professional ethics and auditor training on the performance of auditors in the public accounting firm in Bali. Sampling method in this research was done by using sampling purposive. Respondents in this study are 65 auditors working in KAP in Bali. The number of questionnaires distributed as much as 65 questionnaires. However, the back and can be used for further analysis were 63 questionnaires. Technical analysis of the data used is multiple linear regression analysis with SPSS 15:00 for windows. Based on analysis it can be concluded that the variable of professionalism, professional ethics and auditor training has positive influence on the performance of auditors
Keywords: professionalism, ethics professional, auditor training, performance auditor